Validation of a French Translation of the Altruism Scale for Children - Rose, Lucie; Caetta, Florent; Chokron, Sylvie; Kovarski, Klara (Psychological Test Adaptation and Development, 2023)
Altruistic behavior is a subset of prosocial behavior, aimed at intentionally benefitting another while incurring a cost to the actor. It develops throughout childhood as underlying social–emotional and cognitive mechanisms become mature. Prosocial behavior in childhood is considered as a predictor of later well-being and academic achievement, yet educators and clinicians have few means of measuring it. This study aimed to translate and validate a French version of the Altruism Scale for Children originally developed in English by Swank et al. (2020) that focuses on altruistic behavior with individuals varying in closeness and animals. Children aged 7 through 11 from public and private elementary schools in France ( N = 743), all following the same core curriculum, completed the 30-item questionnaire. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted on the obtained data. The final French version of the Altruism Scale for Children contains 20 questions and distinguishes two facets of altruistic intention, namely, toward close and more distant social contacts. It can be considered as a useful instrument to gain a better understanding of a child’s prosocial behavior throughout contexts.